An Evolving Insight into the Progress of Material Design for Membrane‐Based Electrochemical Lithium Ion Detection. Issue 19 (3rd September 2021) - Bakhtiarvand Bakhtiari, Atousa; Mohammadi, Bahareh; Moazzam, Parisa; Didehroshan, Dorsa; Razmjou, Amir
Abstract: The global shift of energy resources from fossil fuel to renewable energy sources has already begun. The critical energy element of lithium (Li) plays an important role in this energy transition, which is demonstrated by the fast increase in its demand. Rapid and continuous detection of Li has become an important field, as the overexploitation of Li sites, mainly brines, could compromise the nearby aqueous resources that are less salty or contain freshwater. Spent Li‐ion batteries also pose deleterious effects on the environment and aqueous resources. Monitoring of lithium in blood during treating major depressive disorders is also crucial for decreasing the risk of potential lithium toxicity. Li selectivity and stability of membranes as an essential part of any Li sensor is the key to fabricate a high‐performance Li ion‐selective electrode (ISE). Here, the latest progress in Li‐ISEs is covered along with the advanced nanostructured materials that have been recently used for the preparation of Li ion‐selective membranes. The new concepts and technologies that have been created for the purpose of Li mining to be used for Li sensing development are also critically reviewed and highlighted. Abstract : The most important components of ion‐selective electrodes are membranes and the transducer layer. Conducting polymers, carbon and noble metals nanomaterials, and intercalated compounds have been used as ion‐to‐electron transducers for lithium ion‐selective electrodes that are coated by a selective membrane. Recent advances in lithium selective membranes e.g., metal‐organic frameworks, carbon‐based, vermiculite, MXene, and modified polyethylene terephthalate are comprehensively studied.